2006
DOI: 10.3765/bls.v32i1.3442
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Flexibility in the Extension of Novel Causative Verbs

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
(3 reference statements)
0
13
1
Order By: Relevance
“…Alternatively, children and adults might differ in terms of conceptual event encoding: adults, but not children, might have thought that the Results depicted in our pictures were central to the core of a causative event. Consistent with this hypothesis, prior studies have shown that adults have a strong bias for Results when categorizing or learning about causative events (e.g., Papafragou & Selimis, 2010) but children present a mixed picture, taking the activity of an agent (Casasola & Cohen, 2000), the result (Bunger, Baier & Lidz, 2009), or neither/both (Papafragou & Selimis, 2010) to be the core of a causative event. Because there were several differences among these past studies in terms of the stimuli and methods used, this issue remains ripe for further investigation.…”
Section: Resultsmentioning
confidence: 64%
“…Alternatively, children and adults might differ in terms of conceptual event encoding: adults, but not children, might have thought that the Results depicted in our pictures were central to the core of a causative event. Consistent with this hypothesis, prior studies have shown that adults have a strong bias for Results when categorizing or learning about causative events (e.g., Papafragou & Selimis, 2010) but children present a mixed picture, taking the activity of an agent (Casasola & Cohen, 2000), the result (Bunger, Baier & Lidz, 2009), or neither/both (Papafragou & Selimis, 2010) to be the core of a causative event. Because there were several differences among these past studies in terms of the stimuli and methods used, this issue remains ripe for further investigation.…”
Section: Resultsmentioning
confidence: 64%
“…First, children have been shown to use animacy as a cue in verb learning at as early as 2-3 years (Becker, 2007;Bunger & Lidz, 2006). While it is no doubt possible that children have a higher proportion of semantic features misrepresented than phonological ones, and that semantic incompetence makes some contribution to children's performance, it does not seem likely that at this age, these basic semantic features would be so regularly misrepresented.…”
Section: Hypothesis 1: Misrepresentationmentioning
confidence: 99%
“…At roughly 24 months, infants typically begin to add a sizeable number of verbs to their productive lexicons, and use them systematically to refer to actions (e.g., eat, run), mental states (e.g., want, see) and relations (e.g., touch, move). At this point, they also demonstrate a clear capacity to map novel verbs onto categories of events in experimental tasks, and in doing so, they take into account syntactic information, including the number and types of frames in which novel verbs appear and the relations among the noun phrases in these frames, to narrow their hypotheses about possible verb meanings (Akhtar & Tomasello, 1996; Bunger & Lidz, 2006; Fernandes, Marcus, DiNubila, & Vouloumanos, 2006; Fisher, 2002; Gertner, et al, 2006; Gleitman, 1990; Gleitman et al, 2005; Hirsch-Pasek, Golinkoff, & Naigles, 1996; Landau & Gleitman, 1985; Naigles, 1990, 1996). …”
Section: Word-learning In Infancy: Overview Of Evidencementioning
confidence: 99%
“…When the verb was presented in a transitive frame (e.g., “The duck is gorping the bunny”), infants mapped the verb to the causative component (the duck pushing the bunny); when the verb was presented in an intransitive frame (e.g., “The duck and the bunny are gorping”), infants mapped the verb to either the causative or synchronous component. This outcome reveals that infants possess at least some rudimentary knowledge of noun phrases and argument structure (e.g., distinguishing transitive from intransitive constructions) and some rudimentary expectations about how structures map to events (e.g., mapping verbs in transitive constructions to causal rather than merely synchronous events) (Bunger & Lidz, 2004, 2006; Fisher, 1996; Lidz, Gleitman & Gleitman, 2003; Naigles, 1990; Naigles & Kako 1993). In closely related work, infants have also demonstrated their sensitivity to subparts of events, like manner, path, and result (Bunger, 2007; Bunger & Lidz, 2004; Pruden, Hirsh-Pasek, Maguire, & Meyer, 2004; Pulverman, Sootsman, Golinkoff, Hirsh-Pasek, 2003), and to other verb-relevant characteristics like intentionality and telicity (Wagner, 2002; 2006).…”
Section: Word-learning In Infancy: Overview Of Evidencementioning
confidence: 99%